Ekspresi komunikasi bonek dalam membangun citra di masyarakat - Pratama, Panji Jalu; Yenny, Yenny (Universitas Dr.Soetomo, 2020)
This research is titled Bonek communication behavior in building image in the community. Bonek is a football supporter of the Persebaya Surabaya team, supporters are an inseparable part of a football match, people's interest in watching and supporting their respective clubs in the stadium is one a form of loyalty support for the club. In social life Bonek often gets a negative stigma from all forms of behavior, this means Bonek Communication Behavior plays a role in shaping their image in the eyes of the public. This type of research uses qualitative research. Data collection techniques in this study are by interviewing , observation and documentation. Data analysis techniques in this study used two channels consisting of data presentation and drawing conclusions.Keywords:Â behavior, communication, supporters, Bonek, citra.